A new genus of the tribe Praini Mackauer (Hymenoptera: Braconidae: Aphidiinae) from China - Tian, Hong-Wei; Achterberg, Kees Van; Chen, Xue-Xin (Zootaxa, 2017)
A new genus of the tribe Praini Mackauer, 1961 (Braconidae: Aphidiinae) from China is described in this paper, Astigmapraon Tian et Chen, gen. nov. (Type species: A. hei Tian et Chen, sp. nov. from Shaanxi and Sichuan). An identification key to the genera of Praini is added.